Kinetic Resolution of Axially Chiral 5- or 8‑Substituted Quinolines via Asymmetric Transfer Hydrogenation - Wang, Jie; Chen, Mu-Wang; Ji, Yue; Hu, Shu-Bo; Zhou, Yong-Gui (Journal of the American Chemical Society, 2016)
An efficient kinetic resolution of axially chiral 5- or 8-substituted quinoline derivatives was developed through asymmetric transfer hydrogenation of heteroaromatic moiety, simultaneously obtaining two kinds of axially chiral skeletons with up to 209 of selectivity factor. This represents the first successful application of asymmetric transfer hydrogenation of heteroaromatics in kinetic resolution of axially chiral biaryls.